Mutual Fund Advisory Contracts: An Empirical Investigation - Deli, Daniel N. (Journal of Finance, 2002)
ABSTRACT We investigate marginal compensation rates in mutual fund advisory contracts and find the following. Equity and foreign fund advisors receive higher marginal compensation than debt and domestic fund advisors. Advisors of funds with greater turnover receive higher marginal compensation. Also, closedend fund advisors receive higher marginal compensation than open‐end fund advisors. Finally, we find that marginal compensation is lower for advisors of large funds and members of large fund families. We argue that these differences in marginal compensation reflect differences in advisor marginal product, differences in the difficulty of monitoring performance, differences in control environments, and scale economies.